High-dose versus Standard-dose Daunorubicin in Induction Chemotherapy for Acute Myeloid Leukemia: A Meta-Analysis: High- vs Standard-Dose Daunorubicin in AML Induction Therapy - Kulsoom, Bibi; Muhammad Nadeem; Hafiza Touseef Sayyar (Journal of University College of Medicine and Dentistry, 2025)
Objective: This systematic review and meta-analysis aimed to compare the efficacy and safety of high-dose versus standard-dose daunorubicin in induction therapy for adult acute myeloid leukemia (AML), focusing on complete remission (CR), overall survival (OS), and event-free survival (EFS). Methods: PubMed (Medline), Scopus, Science Direct, and Google Scholar were comprehensively and systematically explored for literature published in English, published from inception till January 30, 2025. Eligible studies included RCTs and retrospective cohorts comparing high-dose (>60 mg/m²/day) versus standard-dose (45–60 mg/m²/day) daunorubicin in adult AML patients, reporting at least one of the following outcomes: CR, OS, or EFS. Ten studies met eligibility criteria. Pooled risk ratios (RRs) and 95% confidence intervals (CIs) were calculated using random-effects models. Subgroup analyses were performed based on standard-dose levels (45 vs. 60 mg/m²). Heterogeneity and sensitivity analyses were also conducted. Results: CR rates were numerically higher in the high-dose group but did not reach statistical significance (RR = 1.07; 95% CI: 0.94–1.22; P = 0.32). High-dose daunorubicin significantly improved 1-year OS (RR = 1.14; 95% CI: 1.06–1.23; P = 0.0002) and 5-year OS (RR = 1.32; 95% CI: 1.07–1.63; P = 0.01), especially when compared to the 45 mg/m² dose. While 1-year EFS showed no significant difference, pooled long-term EFS favored the high-dose group (RR = 1.26; 95% CI: 1.01–1.57; P = 0.04). Toxicity profiles were comparable between groups. Conclusion: High-dose daunorubicin improves OS and long-term EFS in adult AML patients, particularly when compared to a standard dose of 45 mg/m², without increasing serious toxicity. It may be preferred in induction regimens where survival benefit is prioritized.